2022
DOI: 10.1186/s41927-022-00263-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omega-three supplementation on serum urate and gout flares in people with gout; a pilot randomized trial

Abstract: Objectives To determine the effect of omega-three supplementation with fish oil on serum urate, weight and body mass index (BMI) in people with gout. Methods A pilot 6-month, randomized, open-label clinical trial was undertaken in people with gout with serum urate ≥ 0.36 mmol/l. Forty participants were randomized to receive 6.2 g omega-3 fish oil daily or no fish oil for 24 weeks. Blood was obtained monthly for serum urate and red cell EPA (20:5n-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Some observational studies also suggested that ω-3 PUFAs, especially DHA were highly related to hyperuricemia ( 13 , 14 ). However, a recent clinical trial found no significant difference in the serum urate level between the 24-week ω-3 PUFAs supplement group and the control group ( 15 ). Since gut microbiota might confer an effect on the host health status by metabolizing PUFAs ( 16 ), we hereby hypothesize a potential mediation effect of gut microbiota on urate metabolism via PUFAs and their important subtypes, such as DHA.…”
Section: Introductionmentioning
confidence: 99%
“…Some observational studies also suggested that ω-3 PUFAs, especially DHA were highly related to hyperuricemia ( 13 , 14 ). However, a recent clinical trial found no significant difference in the serum urate level between the 24-week ω-3 PUFAs supplement group and the control group ( 15 ). Since gut microbiota might confer an effect on the host health status by metabolizing PUFAs ( 16 ), we hereby hypothesize a potential mediation effect of gut microbiota on urate metabolism via PUFAs and their important subtypes, such as DHA.…”
Section: Introductionmentioning
confidence: 99%
“…Fish oil may be a key ingredient in the prevention of gouty attacks, as it is rich in the omega-3 fatty acid, which has been widely reported to have anti-inflammatory activities [32]. Clinical research has found that fish oil supplementation contributes to lower serum uric acid levels and reduces the risk of gout [33,34]. In addition, this study found that poultry intake was a risk factor for gout by using the main method, IVW analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Indirect inferences from other trials were again limited by trial reporting, wherein few trials reported flare rates for both the period during and immediately after prophylactic cessation. Identifying clinical characteristics that may alter an individual's susceptibility to gout flares when initiating or escalating ULT may be a useful approach to tailoring prophylactic use, and although research in this area is expanding, more adequately powered clinical trials to solidify the associations are required 62–66 . Additionally, established risk factors for flares, such as the presence of tophi, require quantifiable measurement by dual‐energy computed tomography 67 or ultrasonography 68 to accurately assess the risk, and access to these in practice may be limited.…”
Section: Discussionmentioning
confidence: 99%